AKUNTANSI ZAKAT FITRAH : KAJIAN PSAK 109 (Study Kasus Pada Masjid Baitul Muqarrabin Punge Blang Cut Banda Aceh) - Maksalmina Maksalmina (University Muhammadiyah Aceh, 2020)
This study aims to analyze the management of zakat in Zakah Fitrah Committee of Baitul Muqarrabin Mosque on implementing Zakah Accounting based on PSAK 109. This is a qualitative research with case study. The data collection technique done through interview. The results showed that Zakah Fitrah Committee of Baitul Muqarrabin Mosque has performed its duties and functions as the Amil Zakat Agency in accordance with decree of Badan Kemakmuran Masjid (BKM) Baitul Muqarrabin. However, the financial statements that have been compiled are not in accordance with the standard contained in PSAK 109 on Accounting for Zakah